VAPYRIN attenuates defence by repressing PR gene induction and localized lignin accumulation during arbuscular mycorrhizal symbiosis of Petunia hybrida - Chen, Min (The New phytologist, 2021)
© 2020 The Authors New Phytologist © 2020 New Phytologist Foundation.